2020
DOI: 10.1159/000506470
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Hemodynamic Profiles during Hemodialysis in Patients with and without Heart Failure

Abstract: Background: Although the dynamics of blood pressure (BP) during dialysis provide information related to the control system, the prognosis and relationships between temporal changes in intradialytic hemodynamic regulation, BP, and decreased cardiac function remain largely unclear. Methods: Hemodynamic parameters, including heart rate (HR), stroke volume (SV), cardiac index, and systemic vascular resistance index, were recorded using a noninvasive hemodynamic device on a beat-by-beat basis in 40 patients on dial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Out of the 28 studies in which UF volume or UF rate were reported, we identified 23 studies, for a total of 43 cohorts which investigated the correlation between the biggest CO changes and UF rate [27, 28, 30, 34, 36, 40, 45, 48, 49, 51‒64]. We found a weak correlation between the change in CO and the UF rate ( r = 0.3, p = 0.05) (shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Out of the 28 studies in which UF volume or UF rate were reported, we identified 23 studies, for a total of 43 cohorts which investigated the correlation between the biggest CO changes and UF rate [27, 28, 30, 34, 36, 40, 45, 48, 49, 51‒64]. We found a weak correlation between the change in CO and the UF rate ( r = 0.3, p = 0.05) (shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 2 illustrates the geographical distribution of USPD usage. The timing of KRT initiation in AKI is vital, as any delay may lead to a poorer prognosis for the patient [80,81].…”
Section: Peritoneal Dialysis In Management Of Acute Kidney Injurymentioning
confidence: 99%
“…Moreover, peritoneal dialysis was also considered hemodynamically stable in contrast to hemodialysis; thus, it was more commonly used in hemodynamically unstable patients [42,76,81].…”
Section: Underlying Comorbidities In Akimentioning
confidence: 99%